FAKTOR-FAKTOR PENGAMBILAN KEPUTUSAN WISATAWAN UNTUK BERKUNJUNG KE OBJEK WISATA ISTANA SIAK SRI INDRAPURA KABUPATEN SIAK PROVINSI RIAU - Analis Eryani; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research of purpose to determine the response of tourist about decision-making factors of tourist to visit Siak Sri Inderapura Palace tourism object.This research used descriptive quantitative. There are100 sample were taken using accidental sampling. Data collection techniques in this research using observation, interviews, questionnaires, and documentation. The using likert scale as a measurement tool for determine the short length of the interval that can be used to generate quantitative data.Factors that influence the decision making process, namely tourist characteristics, the awareness of the benefits of travel, description of the tour and tourist destination of excellence (Pitana dan Gayatri, 2005). From the result of research, according to responses by tourist the factor of tourist destination of excellence is a very determining faktor in the proses of decision making to visit Siak Sri Indrapura Palace tourism object.Keyword : decision making factors, tourist, tourism object